Counterion binding on coacervation of dioctyl sulfosuccinate in aqueous sodium chloride. Issue 18 (24th April 2019) - Wang, Shengbo; Chen, Changlong; Shiau, Bor-Jier; Harwell, Jeffrey H.
Abstract : A simple coacervate-forming system consisting of sodium dioctyl sulfosuccinate (DOSS) in aqueous NaCl solution was investigated by turbidity measurement, electromotive force measurement (EMF), dynamic light scattering (DLS), and cryogenic transmission electron microscopy (cryo-TEM) to reveal the role of counterion binding in the microstructural changes behind the evolution of the coacervate phase. Abstract : A simple coacervate-forming system consisting of sodium dioctyl sulfosuccinate (DOSS) in aqueous NaCl solution was investigated by turbidity measurement, electromotive force measurement (EMF), dynamic light scattering (DLS), and cryogenic transmission electron microscopy (cryo-TEM) to reveal the role of counterion binding in the microstructural changes behind the evolution of the coacervate phase. Coacervation phase boundaries of DOSS against different NaCl concentrations were obtained; the pseudo-coacervation constant, K sp, co = [DOSS − ][Na + ], was determined to be 1.35 ± 0.15 × 10 −4 M 2 at 25 °C. Sodium ion activity from EMF measurements confirmed a drastic rise in counterion binding to DOSS aggregates near the coacervate phase boundary. For DOSS/NaCl solution concentrations near the coacervate phase boundary, the turbidity changed, starting from a clear, isotropic solution far from the phase boundary, transitioning to a turbid solution near the phase boundary, and exhibiting a distinct growth of the hydrodynamic diameter of DOSS aggregates as detected by DLS. Cryo-TEM evidenced the presence of vesicles at concentrations close to the coacervate phase boundary; both unilamellar and multilamellar vesicles were observed. Increased counterion binding on the aggregates led to fusion of the larger vesicles and eventually to formation of a coacervate phase; the DOSS aggregates in the clear supernatant phase were predominately small vesicles of approximately 100 nm diameter. This study suggests that the mechanism for coacervate formation in DOSS solutions is an increase in counterion binding coincident with formation of multilamellar vesicles near the phase boundary, followed by flocculation of the multilamellar vesicles beyond the phase boundary to form the coacervate phase.